Implementasi Digital Fundraising Zakat Berdasarkan UU No. 23 Tahun 2011 Perspektif Donatur dan Pengelola - Abdullah Sani Harahap; Sandy Rizki Febriadi (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. The development of digital technology has driven changes in zakat management, particularly in fundraising mechanisms through digital platforms. This study is motivated by the need for zakat institutions to adapt to digital banking technologies and to comply with Law Number 23 of 2011 on Zakat Management. The study aims to analyze the conformity of digital fundraising practices with national legal provisions, examine donors’ perceptions of the effectiveness of digital services, and identify the strategies implemented by Lazismu West Java in optimizing technology-based zakat collection. This research employs a qualitative approach using semi-structured interviews, observation, and document analysis. Data were collected from Lazismu West Java managers, donors who utilize digital services, as well as regulatory sources and academic literature. The findings indicate that the use of QRIS, mobile banking, and virtual accounts is perceived as effective and practical, and contributes to increased transparency and accountability in zakat management. Donors generally express positive perceptions of digital fundraising, although challenges remain in terms of digital literacy and human resource competencies. This study concludes that digital fundraising practices are in accordance with Law Number 23 of 2011 and have the potential to enhance donor participation through strengthened education and management systems. Abstrak. Perkembangan teknologi digital telah mendorong perubahan dalam pengelolaan zakat, khususnya pada mekanisme penghimpunan dana melalui digital fundraising. Penelitian ini dilatarbelakangi oleh tuntutan adaptasi lembaga amil zakat terhadap teknologi perbankan digital serta kewajiban kepatuhan terhadap Undang-Undang Nomor 23 Tahun 2011 tentang Pengelolaan Zakat. Penelitian ini bertujuan menganalisis kesesuaian praktik digital fundraising dengan ketentuan hukum nasional, menilai persepsi donatur terhadap efektivitas layanan digital, serta mengidentifikasi strategi Lazismu Jawa Barat dalam mengoptimalkan penghimpunan zakat berbasis teknologi. Penelitian menggunakan pendekatan kualitatif melalui wawancara semi terstruktur, observasi, dan telaah dokumen. Data diperoleh dari pengelola Lazismu Jawa Barat, donatur pengguna layanan digital, serta sumber regulasi dan literatur akademik. Hasil penelitian menunjukkan bahwa pemanfaatan QRIS, mobile banking, dan virtual account dinilai efektif, praktis, serta meningkatkan transparansi dan akuntabilitas pengelolaan zakat. Donatur memberikan persepsi positif terhadap digital fundraising, meskipun masih ditemui kendala pada aspek literasi digital dan kompetensi sumber daya manusia. Penelitian ini menyimpulkan bahwa digital fundraising sejalan dengan Undang-Undang Nomor 23 Tahun 2011 dan berpotensi meningkatkan partisipasi donatur melalui penguatan edukasi dan sistem pengelolaan.